Mental Health of Parents having Children with Congenital ENT Defects - Raja Muhammad Shoaib , Tallat Najeeb,Muhammad Ajmal (Journal of Rawalpindi Medical College, 2015)
Background: To determine the frequency of psychological and mental problems among parents of children with congenital ENT diseases and to get an idea about the magnitude of mental health issues of such parents. Methods: In this cross-sectional study parents of the children with congenital ENT defects were included. General Health Questionnaire version 12 (GHQ-12) was used to ascertain their mental health status at that time. Out of a possible score range of 0-12, 4 was the cut off score.Those with scores 4 or above were considered to have mental health problems. Those scoring 4-6 were labeled mild, 6-8 and above 8 were categorized as having moderate and severe mental health problems respectively. The questionnaires were completed on the same day, even if the subjects needed help. Results: Total parents were 31, of which 18(58%) were male and 13(41%) were female. Fourteen (45%) out of 31 parents developed different types of psychiatric illness with different degree of severity. Fourteen out of 31 tested were positive. Four respondents were mild (score 4-6), three were moderate (score 6-8) and seven were severe (score>8). Five out of 7 severe cases were women. Chi square test was applied and results were significant (p value <0.05%). Conclusion: Birth of a congenitally defected child does have adverse effects on parents’ mental health and more so for mothers.